Η καινοτομία των Ερευνητικών Εργασιών στην πράξη: Οι απόψεις των εκπαιδευτικών για την εφαρμογή της στην Α΄ Τάξη του Γενικού και Επαγγελματικού Λυκείου στο Νομό Δωδεκανήσου - Αργυρίου Αργύρης; Κασιμάτη Αικατερίνη; Ανδρεάδου Δέσποινα (Παιδαγωγικά ρεύματα στο Αιγαίο, 2022)
This paper elaborates and analyzes the results of an empirical survey in order to investigate teachers working in Dodecanese prefecture views, regarding implementation of research work in practice, in Class A of the General and Vocational School. The specific survey’s objectives was to explore in which extent the four pedagogical principles for research work apply to: a) the principle of the research approach in learning, b) the principle of teacher’s collaboration, c) the principle of differentiation in learning content, process and context, d) the principle of student’s team working. An additional objective of this study was to record teachers views regarding the problems encountered during the research implementation process as well as select their recommendations to resolve them.